2016
DOI: 10.1016/j.matdes.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced piezoelectric properties in potassium-sodium niobate-based ternary ceramics

Abstract: 1-x)K 0.5 Na 0.5 Nb 1-y Sb y O 3 -zSrZrO 3 -xBi 0.5 Na 0.5 HfO 3 (KNNS-SZ-BNH) lead-free ceramics were developed by the conventional solid-state reaction method. Effects of the additives (Bi 0.5 Na 0.5 HfO 3 , SrZrO 3 and Sb 5+ ) on their phase structure, microstructure, and electrical properties were investigated. The rhombohedral-orthorhombic-tetragonal (R-O-T) phase boundary can be established in the ceramics with 0.03≤x≤0.05, 0.04≤y≤0.06, and 0.01≤z≤0.025, and then their piezoelectric properties were impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…4 Here, both the R-T phase boundary and the ferroelectric domains were responsible for the enhancement of the piezoelectric properties. 28 Generally, both the dielectric and the ferroelectric properties play a role in the piezoelectric properties of ferroelectric materials, according to the relationship d 33 ∝ ae r P r , where a is the electrostrictive coefficient, ɛ r is the relative dielectric constant, and P r is the remanent polarization (P r is shown in Figure S8C-D). Furthermore, as discussed above, the ceramics possessing an R-T phase boundary exhibited an easy ferroelectric domain switching, which also increased the net piezoelectricity.…”
Section: Ferroelectric Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Here, both the R-T phase boundary and the ferroelectric domains were responsible for the enhancement of the piezoelectric properties. 28 Generally, both the dielectric and the ferroelectric properties play a role in the piezoelectric properties of ferroelectric materials, according to the relationship d 33 ∝ ae r P r , where a is the electrostrictive coefficient, ɛ r is the relative dielectric constant, and P r is the remanent polarization (P r is shown in Figure S8C-D). Furthermore, as discussed above, the ceramics possessing an R-T phase boundary exhibited an easy ferroelectric domain switching, which also increased the net piezoelectricity.…”
Section: Ferroelectric Domainsmentioning
confidence: 99%
“…We obtained the optimal dielectric properties (e.g., ɛ r~2 240 and tan d~0.04) in the ceramics with x = 0.03 and y = 0.035 due to the R-T phase boundary. 28 Generally, both the dielectric and the ferroelectric properties play a role in the piezoelectric properties of ferroelectric materials, according to the relationship d 33 ∝ ae r P r , where a is the electrostrictive coefficient, ɛ r is the relative dielectric constant, and P r is the remanent polarization (P r is shown in Figure S8C-D). 29,30 The equation indicates that d 33 and ɛ r P r should display a similar variation.…”
Section: Ferroelectric Domainsmentioning
confidence: 99%
“…As x further increased up to 0.035, TR-O and TO-T overlapped with each other, leading to the formation of an R-T phase boundary at TR-T [23,25,26]. The TR-T of the ceramics with x=0.035 and 0.04 was very near room temperature at 31±20 o C and 5±5 o C, respectively, suggesting the coexistence of the R and T phases at the room temperature [23,25,26]. For the ceramics with x=0.05, its TR-T of -4 o C was much lower than room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, some authors reported that the addition of (Bi 0.5 Na 0.5 )HfO 3 in KNN could lead to the formation of phase boundary as well as a remarkable enhancement of piezoelectric properties. Therefore, in this current work, we prepared the (1‐ x )(K 0.48 Na 0.48 Li 0.04 )Nb 0.95 Sb 0.05 O 3 ‐ x (Bi 0.5 Na 0.5 )HfO 3 [abbreviated as (1‐ x )KNLNS‐ x BNH] ceramics by a conventional solid‐state reaction route.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,19 Hence in order to construct a phase boundary in KNN-based materials, one or both of the two phase-transition temperatures, known as T R-O and T O-T , respectively, should be adjusted to around room temperature through the addition of some other ions or ABO 3 -type compounds. 6 Very recently, some authors [20][21][22][23] reported that the addition of (Bi 0.5 Na 0.5 )HfO 3 in KNN could lead to the formation of phase boundary as well as a remarkable enhancement of piezoelectric properties. Therefore, in this current work, we prepared the (1-x)(K 0.48 Na 0.48 Li 0.04 ) Nb 0.95 Sb 0.05 O 3 -x(Bi 0.5 Na 0.5 )HfO 3 [abbreviated as (1-x) KNLNS-xBNH] ceramics by a conventional solid-state reaction route.…”
Section: Introductionmentioning
confidence: 99%